2009
DOI: 10.1073/pnas.0911331106
|View full text |Cite
|
Sign up to set email alerts
|

Theta–gamma coupling increases during the learning of item–context associations

Abstract: Phase-amplitude cross-frequency coupling (CFC) between theta (4 -12 Hz) and gamma (30 -100 Hz) oscillations occurs frequently in the hippocampus. However, it still remains unclear whether thetagamma coupling has any functional significance. To address this issue, we studied CFC in local field potential oscillations recorded from the CA3 region of the dorsal hippocampus of rats as they learned to associate items with their spatial context. During the course of learning, the amplitude of the low gamma subband (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

66
793
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 850 publications
(867 citation statements)
references
References 34 publications
66
793
2
6
Order By: Relevance
“…According to an influential computational model (Lisman and Idiart, 1995;Jensen and Lisman, 1998;Lisman, 2010), maintenance is enabled by a cross-frequency coupling of gamma-(30 -80 Hz oscillations) related neural spiking to specific phases of ongoing hippocampal theta oscillations (4)(5)(6)(7)(8). In agreement with this model, theta/ gamma coupling has been observed in relation to sequential (Axmacher et al, 2010) and spatial (Tort et al, 2009) shortterm memory. Fuentemilla et al (2010) investigated theta-coupled periodic replay during short-term memory maintenance using wholehead magnetoencephalographic (MEG) recordings.…”
Section: Introductionsupporting
confidence: 67%
“…According to an influential computational model (Lisman and Idiart, 1995;Jensen and Lisman, 1998;Lisman, 2010), maintenance is enabled by a cross-frequency coupling of gamma-(30 -80 Hz oscillations) related neural spiking to specific phases of ongoing hippocampal theta oscillations (4)(5)(6)(7)(8). In agreement with this model, theta/ gamma coupling has been observed in relation to sequential (Axmacher et al, 2010) and spatial (Tort et al, 2009) shortterm memory. Fuentemilla et al (2010) investigated theta-coupled periodic replay during short-term memory maintenance using wholehead magnetoencephalographic (MEG) recordings.…”
Section: Introductionsupporting
confidence: 67%
“…Results from recent studies in both animals and humans support a mechanism that oscillations at higher frequencies are often modulated by the phase of slower phase fluctuations (Osipova et al, 2008;Tort et al, 2008Tort et al, , 2009Tort et al, , 2010Cohen et al, 2009a, b;Colgin et al, 2009;Axmacher et al, 2010a, b;Voytek et al, 2010). Important elements of nonlinear coupling across different frequencies reveal different types of CFC, such as phase-amplitude coupling (Tort et al, 2008(Tort et al, , 2009(Tort et al, , 2010Cohen et al, 2009a,b;Colgin et al, 2009;Axmacher et al, 2010a,b), n:m phase locking (Dimitriadis et al, 2015b), and amplitude-amplitude coupling (Hipp et al, 2012;Engel et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…There is ample evidence that the last type of CFC, also called phase-amplitude modulation, occurs very often in both animals and humans in the prefrontal cortices, the hippocampus, and other distributed cortical areas (Osipova et al, 2008;Tort et al, 2008Tort et al, , 2009Tort et al, , 2010Cohen et al, 2009a, b;Colgin et al, 2009;Axmacher et al, 2010a, b;Voytek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from rodents suggests that theta/gamma coupling could be functionally important for long-term memory processes (Tort, Komorowski, Manns, Kopell, & Eichenbaum, 2009). In this study, as learning of the association between context and food reward location progressed, the animals showed an increase in cross-frequency coupling which the strength of coupling predicting the probability of correct choice.…”
Section: Theta Gamma Code In Memorymentioning
confidence: 75%
“…Similarly to the present study, a number of human and animal studies have demonstrated a relationship between theta power and coherence, as well as gamma and theta/gamma coupling at both medial temporal lobe and other neocortical sites in relation to information processing (Fell et al, 2001(Fell et al, , 2003Sederberg et al, 2003;Canolty et al, 2006;Tort et al, 2009;Shirvalkar et al, 2010, Colgin et al, 2009). The findings provided here suggest that (1) …”
Section: Discussionmentioning
confidence: 95%